2001
DOI: 10.1046/j.1469-0691.2001.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Extra-intestinal infections caused by Clostridium difficile

Abstract: The objective of this paper was to investigate the incidence of extra-intestinal infections caused by Clostridium difficile. During a 10-year period, the microbiology laboratory of our institution isolated 2034 isolates of C. difficile. Of the 2034 isolates, 21 (1.08%) were obtained from extra-intestinal sources. This represents an incidence of extra-intestinal isolation of four cases per 100 000 admissions. We were able to review the records of 17 patients for our study. The isolates in 12 patients were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
72
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 31 publications
0
72
0
2
Order By: Relevance
“…In our patient, colonoscopy performed after intensive antibiotic therapy for septic shock showed pseudomembranous colitis, which is well known to be caused by C. difficile infection, but stool toxin testing and blood cultures were negative. García-Lechuz et al 8) reported that extracolonic C. difficile infection does not always produce toxins, and that blood cultures are…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, colonoscopy performed after intensive antibiotic therapy for septic shock showed pseudomembranous colitis, which is well known to be caused by C. difficile infection, but stool toxin testing and blood cultures were negative. García-Lechuz et al 8) reported that extracolonic C. difficile infection does not always produce toxins, and that blood cultures are…”
Section: Discussionmentioning
confidence: 99%
“…Si bien, se han publicado casos aislados o series cortas 1,2 , el resto de las comunicaciones son escasas y muy heterogéneas.Objetivos: Evaluar la relevancia clínica de la infección extra-intestinal por Clostridium difficile (IECD) en una institución de salud, describiendo el manejo de estas raras infecciones y sus resultados.Método: Se realizó una revisión retrospectiva de registros médicos de la Clínica Mayo Rochester para identificar a los pacientes con aislamiento de CD en sitios extra-intestinales entre los años 2004 y 2013. Se extrajeron datos como las características demográficas, cultivos microbiológicos, asociaciones clínicas y resultados del manejo de tales infecciones.…”
unclassified
“…Si bien, se han publicado casos aislados o series cortas 1,2 , el resto de las comunicaciones son escasas y muy heterogéneas.…”
unclassified
“…C. perfringens is the Clostridium species most frequently isolated from blood culture, and Clostridium septicum is the Clostridium species most frequently isolated from intra-abdominal specimens (2, 4, 5, 16). Bone infection is uncommon: to the best of our knowledge, C. difficile is the bacterium most frequently isolated from bone specimens (4,5,14,16,26). However, no more than six cases of clearly established osteomyelitis due to Clostridium spp.…”
mentioning
confidence: 99%
“…However, no more than six cases of clearly established osteomyelitis due to Clostridium spp. have been reported (14). As is true for other endogenous infections due to anaerobes, the development of clostridial disease is usually associated with common predisposing factors, including underlying illness such as cancer, leukemia, and diabetes mellitus (2).…”
mentioning
confidence: 99%